Fate of dredged contaminated sediments in an underwater disposal site - Carpentier, S.; Moilleron, R.; Thevenot, D.R. (Characterization of Contaminated Sediments, 2002)
In the Seine basin (France), dredged sediments are stored in disused quarries under a layer of water. The disposal site of Rouillard used for the storage of dredged sediments since July 1999 was investigated. The aim of this research was to assess the impact of this type of management on the environment. The quality of both free water and sediment was monitored before and after the first deposits in July 1999. So far, the storage of dredged material (DM) in this underwater disposal site leads to a decrease of the pond water quality. High NH4+ concentrations, resulting from diagenetic processes occurring within the dredged material, once settled, were observed. Micro-pollutants such as heavy metals or PAHs present no significant release in the pond water, but their content inside the surface pond sediment increase with time.